VEGFR inhibitors upregulate CXCR4 in VEGF receptor-expressing glioblastoma in a TGFβR signaling-dependent manner. Issue 1 (28th April 2015) - Pham, Kien; Luo, Defang; Siemann, Dietmar W.; Law, Brian K.; Reynolds, Brent A.; Hothi, Parvinder; Foltz, Gregory; Harrison, Jeffrey K.
Highlights VEGFRs are heterogeneously expressed by glioblastoma stem-like cells. VEGFR inhibitors increase GBM CXCR4 and enhance functional responses to CXCL12. Combination of VEGFR and CXCR4 inhibitors slows progression of GBM xenografts. Upregulation of GBM CXCR4 by VEGFR inhibitors is TGFβR signaling dependent.